Piece by Piece: Exploring the Origins of the Philistines - Master, Daniel M. (Biblical archaeology review, 2022)
The Philistines have gone down in history as ancient Israel’s archenemy. Yet they were much more than that. We have uncovered their cities, temples, houses, weapons, tools, and pots—and, recently, remains of the Philistines themselves. Thanks to new DNA analysis, we now can answer questions about the Philistines’ origins. (Ed. note: This article contains images of human skeletal remains.)